The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11030-021-10214-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based identification of SARS-CoV-2 main protease inhibitors from anti-viral specific chemical libraries: an exhaustive computational screening approach

Abstract: Worldwide coronavirus disease 2019 (COVID-19) outbreak is still threatening global health since its outbreak first reported in the late 2019. The causative novel virus has been designated as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Although COVID-19 emergent with significant mortality, there is no availability of definite treatment measures. It is now extremely desirable to identify potential chemical entities against SARS-CoV-2 for the treatment of COVID-19. In the present study, a state-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The virtual screening and molecular docking study were also conducted against the main protease of SARS-CoV-2 by taking FDA-approved drugs from the ZINC database where they have found binding energy ranges from −7.8 to −6.839 kcal/mol [99], whereas we have found epicatechin-3-O-gallate, psi-taraxasterol, and catechin gallate having binding affinities of −8.4, −8.5, and −8.8 kcal/mol. Additionally, multiple studies regarding the virtual screening and molecular docking were conducted by targeting the main protease of SARS-CoV-2 where several interactions at the active points Thr26, Leu41, Cys145, Pro168, Asn142, His164, Met49, Phe140, Met165, Glu166, Gln189, and Thr190 [99][100][101][102][103] were observed, which is similar to our findings.…”
Section: Discussionsupporting
confidence: 87%
“…The virtual screening and molecular docking study were also conducted against the main protease of SARS-CoV-2 by taking FDA-approved drugs from the ZINC database where they have found binding energy ranges from −7.8 to −6.839 kcal/mol [99], whereas we have found epicatechin-3-O-gallate, psi-taraxasterol, and catechin gallate having binding affinities of −8.4, −8.5, and −8.8 kcal/mol. Additionally, multiple studies regarding the virtual screening and molecular docking were conducted by targeting the main protease of SARS-CoV-2 where several interactions at the active points Thr26, Leu41, Cys145, Pro168, Asn142, His164, Met49, Phe140, Met165, Glu166, Gln189, and Thr190 [99][100][101][102][103] were observed, which is similar to our findings.…”
Section: Discussionsupporting
confidence: 87%
“…For grid generation in the case of Mpro, the information of the catalytic active site and substrate binding site residues coordinates was used as −12.0, 18.0, 65.0 Å along X-, Y- and Z-axes, respectively whereas dimension was considered as 26 × 28 × 30 Å respectively. During grid generation, careful inspection and confirmation of catalytic site residues (such as His41 and Cys145) and substrate binding site residues at an active site within the grid box were carried out [ 28 ]. The output of molecular docking poses generated for each ligand against the respective targets were ranked and selected among ligand-protein complex based on the docking scores.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, M pro necessitates the catalytic dyads Cys 145–His 41 to cleave SARS-CoV-2 polyproteins. 42,44 Hence, the interaction with the catalytic residues (His41and Cys145) is an attractive target for inhibition. Furthermore, it has been shown that the Cys44 to Pro52 residues constitute the catalytic loop, which forms the catalytic pocket, a loop that surrounds the cavity of the catalytic site in M pro .…”
Section: Resultsmentioning
confidence: 99%